O metabolismo entre homem e natureza: um estudo ecológico e histórico da vida humana e não-humana na sociedade capitalista - Castillo, Beatriz França (Universidade Federal de São Carlos, 2021)
The present work is an effort to understand the specifically capitalist origin of the ecological problems of our time. Presenting a historical review of the relationship between human and nature, it is demonstrated how the establishment of capitalism modifies the way in which material and energy exchanges are carried out between society and the environment. From these changes we can point out the worker's alienation from the land and his means of work and therefore his distance from nature itself, the interference in natural cycles with the separation of large-scale agriculture and large industry in the countryside and cities respectively, as well as the orientation of production being given through the search for the maintenance of the profit rate and not through attending the humanity needs. Such are the contradictions that Capital created and that are verified through ecological data such as biological diversity, population density and distribution, as well as concentration of nutrients and pollutants. The conclusion that is pointed out is that the very dynamics of Capital have historically developed in contradiction with ecological homeostasis and this contradiction is increasingly expanding and aggravating. The search for a solution to environmental problems must necessarily permeate a political-economic understanding of capitalism on the way to overcoming it.
The metabolism between man and nature: an ecological and historical study of human and non-human life in capitalist society
Keywords: Ecologia marxista; Crise ambiental; Biologia dialética; Capitalismo; Marxist ecology; Environmental crisis; Dialectical biology; Capitalism; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS HUMANAS::CIENCIA POLITICA; CIENCIAS HUMANAS::FILOSOFIA